Pengaruh Corporate Social Responsibility, Ukuran Perusahaan, Dan Leverage Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur - Shafira, Adelia; Guritno, Y.; Ermaya, H.N.L. (Jurnal Akunida, 2022)
Tax avoidance is an act of a company by taking advantage of weaknesses in government regulations to reduce the tax burden issued by the company. This study was conducted to test and provide empirical evidence of the influence of Corporate Social Responsibility, the size of the company and leverage on tax avoidance in manufacturing companies on the Indonesia Stock Exchange in the 2016-2019 period. The variables used in this study are Corporate Social Responsibility, company size, leverage and tax avoidance. The research population of this company is 180 manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. The sample selection using the purposive sampling method is the determination of the sample based on predetermined criteria, so that the number of samples obtained is 71 samples of companies with a total of 190 samples. after elimination. The data in this study is secondary data obtained from the annual report through the website (www.idx.co.id). The data of this research were collected by using documentation technique. The results of this study show that partially CSR has no effect on tax avoidance, firm size has a significantly negative effect and leverage has a significantly positive effect on tax avoidance.